Keluhan Sebagai Bentuk Partisipasi - Erwan Agus Purwanto (JKAP (Jurnal Kebijakan dan Administrasi Publik), 2008)
To get equal access to good-quality public service is the right of every citizen. Unfortunately, the quality of public service in Indonesia is still far below the expectation of the people. Corruption practice is the main factor to be blamed as the source of the problem in this case. There are many ways to improve the quality of public service. One of them is to encourage the awareness of people to complain when he/she feels unsatisfied with the quality of public services provided by the government. To facilitate people to complain many developed countries establish an institution that is called ombudsman. This article discusses the effectiveness of local ombudsman of Yogyakarta Special Province in channeling the people's complaints as the way to improve teh quality of public services in this province.